L’enterrement d’une triade divine féminine à Lugdunum : étude du dépôt de la place d’Albon à Lyon (Métropole de Lyon) - Lucas Guillaud; Emmanuel Bernot; Aline Colombier-Gougouzian; Amaury Gilles; Nicolas Garnier (Gallia)
Archaeological investigations carried out between 2014 and 2020 on the Place d’Albon in the 2nd arrondissement of Lyon (France) revealed the existence of an evolving settlement along the left bank of the Saône. A large warehouse built at the beginning of the 2nd century AD has been uncovered. It consists of several cells in a row with wooden floors, bordered by a passage. The building was rebuilt several times before being abandoned in the 3rd century AD. In these levels of destruction and abandonment, a pit was discovered that contained what appears to be a deposit of exceptional archaeological material. It was sealed with a large marble slab and marked in the landscape by a tile placed on edge on the wall of the horreum.The collection comprises a large bronze vessel that serves as a container for other objects. It is a situla with a carved lip, similar to numerous other examples found in the Roman world among collections of archaeological objects from the 3rd century. Physical and chemical analysis of the residues –notably animal meat, wine, pitch and millet– found at the bottom of the vessel indicates that it was used for cooking.Inside the situla, a bronze cup (Bienert 69 type) and a glass flask (Isings 104b type) were discovered. These two containers were found resting on a bronze bench, on which three statuettes of seated goddesses were also placed. The three statuettes are similar in appearance and carry the same attributes –a cornucopia in one arm, a flat patera in one hand, and a headdress adorned with a diadem. These elements give the goddesses similarities with other patron gods such as Fortuna, Abundance, Tutela, but also Lares and Genii. The clothing is relatively simple and schematic, perhaps reflecting a simplification of the palla and stola by the craftsman. The Lyon group of three mother goddesses seated on a bench is therefore, to our knowledge, a unique example of Roman small sculpture. No group of three of this type is recorded in the scientific literature, although some isolated statuettes have similar characteristics to our objects. Finally, only the stelae provide us with convincing comparative examples.The worship of mother goddesses was prevalent in the Western Roman world, particularly in the Bonn or Köln region where it was of significant importance. The cult was organised in curiae and revered in major temples. As tutelary goddesses, they usually appeared in threes and were often associated with a particular geographical area or ethnic group, as evidenced by the Celtic or Germanic epithets that accompanied them. The capital of Gallia Lugduniensis is well known for its cult, which is evidenced by the discovery of three figural representations and ten inscriptions. In Lyon, most dedications are made by individuals who add the epiclesis Augusta to the name of the deities, known as the Matrae. This adjective emphasizes the official character of the cult. The Matrae Augustae are believed to be the expression of important local beliefs and traditions, with the title Augustus serving as recognition of this reality by the local authorities.The deposit raises questions. It belongs to a period in the 3rd century when numerous “treasures” or “deposits” were discovered. However, unlike the large finds of Dury, Bavay, Neupotz or Hagenbach, the Lyon find is very homogeneous. Based on the evidence collected, it seems that the items examined might have been part of a small cult space located within the warehouse. Similar examples found in Italy, including Rome and Ostia, as well as in other areas, suggest that horrea often contained sacred spaces associated with patron deities like Fortuna, Bona Dea, Sol, Silvain, Liber Pater, and Genius horreorum. This leads us to believe that it is possible that someone who frequented or worked at the warehouse sought protection from the Mothers, who were called upon to safeguard and preserve places near the banks of the Saône, much like genii loci.There remains the question of the actual burial of these objects. When the building was abandoned, they were relocated, carefully placed in a pit and sealed with a marble slab. While this practice seems quite unusual for a building that had a primarily economic function, this is not the case in the cultic field. Similar practices have been encountered in sanctuaries, such as Le Vieil-Évreux or Genainville. It is believed that these sealed pits were used for specific rituals associated with the closure and abandonment of sacred spaces. The remains found in Place d’Albon probably reflect part of a deliberate and precise sequence which, although incomplete based solely on archaeological evidence, closely resembles funerary rites.